2006
DOI: 10.1073/pnas.0601712103
|View full text |Cite
|
Sign up to set email alerts
|

Vta1p and Vps46p regulate the membrane association and ATPase activity of Vps4p at the yeast multivesicular body

Abstract: endosome ͉ ESCRT complexes ͉ protein sorting ͉ Vps ͉ class E

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(129 citation statements)
references
References 32 publications
5
122
2
Order By: Relevance
“…As will be described below, we confirmed in parallel studies that LIP5 also binds to CHMP5 with comparable or even higher affinity (see Figure 8). The interaction of LIP5 with CHMP1B might have been anticipated based on earlier studies in yeast (Lottridge et al, 2006), but the association of LIP5 with the core ESCRT-III proteins CHMP2A and CHMP3 was unexpected and raises the possibility of a more intimate relationship between LIP5 and ESCRT-III than previously appreciated.…”
Section: Interactions Between Lip5 and Escrt-iii Proteinsmentioning
confidence: 71%
See 2 more Smart Citations
“…As will be described below, we confirmed in parallel studies that LIP5 also binds to CHMP5 with comparable or even higher affinity (see Figure 8). The interaction of LIP5 with CHMP1B might have been anticipated based on earlier studies in yeast (Lottridge et al, 2006), but the association of LIP5 with the core ESCRT-III proteins CHMP2A and CHMP3 was unexpected and raises the possibility of a more intimate relationship between LIP5 and ESCRT-III than previously appreciated.…”
Section: Interactions Between Lip5 and Escrt-iii Proteinsmentioning
confidence: 71%
“…A previous study demonstrated that LIP5 bound efficiently but apparently uniquely to the ESCRT-III like protein CHMP5 (Ward et al, 2005); this interaction was also found in a reciprocal immunoprecipitation of proteins that bind to CHMP5 (Ma et al, 2007). In yeast, Vta1p, the LIP5 orthologue, binds both to Vps60p (CHMP5 ortholog; Shiflett et al, 2004;Azmi et al, 2006;Rue et al, 2007) and to Did2p/Vps46p (CHMP1 ortholog; Lottridge et al, 2006). On this basis, we asked whether LIP5 also interacts with other human ESCRT-III proteins.…”
Section: Lip5 Binds Tightly To Several Escrt-iii Proteins In Additionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vta1 stimulation of Vps4 occurs through both the Vta1 VSL domain and the neighboring VSE (31,53). The VSL domain binds to the Vps4 ␤-domain to promote oligomerization and stimulate ATP hydrolysis (39,40,41,43,55). An additional level of Vps4 stimulation is mediated by the VSE, and the VSE is also required for the enhanced stimulation that occurs when ESCRT-III subunits bind to the amino-terminal MIT domains of Vta1 (53).…”
Section: Discussionmentioning
confidence: 99%
“…We found that mutation of either VPS68 or VPS55 similarly slows the transit of biosynthetic and endocytic cargo proteins through the MVB, but does not block the formation of intralumenal vesicles or cause the accumulation of an aberrant protease-active compartment. A subset of class E vps mutants (including did2/fti1/vps46, vps60, and vta1) that affect ESCRT function by regulating the AAA ATPase Vps4p exhibit mild CPY-sorting defects (Ͻ20%) and partial impairment of lumenal MVB vesicle formation (Azmi et al, 2006;Lottridge et al, 2006). Our results do not preclude a similar role for the Vps55/68 complex in regulating ESCRT proteins and increasing the efficiency of lumenal vesicle formation; however, the strong CPY-sorting defects of vps55 and vps68 mutants suggest they have a different function.…”
Section: The Vps55/68 Complex Is Required For Two Transport Steps Outmentioning
confidence: 99%